2020
DOI: 10.7150/jca.47111
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide (ATO) induced degradation of Cyclin D1 sensitized PD-1/PD-L1 checkpoint inhibitor in oral and esophageal squamous cell carcinoma

Abstract: Arsenic trioxide (ATO) is widely studied for its antitumor efficacy and several recent studies suggested the immune modulatory effects of ATO in animal models. In this study we found ATO treatment induced increased ROS production and DNA damage in esophageal squamous cell carcinoma (ESCC) cells, led to DNA damage mediated degradation of Cyclin D1 and upregulation of PD-L1 in these cancer cells. Mechanistically, we found ATO induced a transient upregulation and nuclear translocation of Cyclin D1 by sumoylation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Specially ATO inhibited T-cell-mediated autoimmunity by inhibiting the proliferation of T lymphocytes, inducing CD4 + T-cell apoptosis and increasing the proportion of immunoinhibitory T reg cells, and its application may improve the clinical outcome of patients with severe aplastic anemia. 18,19 Additionally, Zhu et al 9 demonstrated that ATO induced the upregulation of PD-L1 in oral squamous carcinoma cells. Consistent with previous studies, we found that ATO significantly upregulated the expression of PD-L1 at both the protein and mRNA levels in NB4 and Jurkat cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specially ATO inhibited T-cell-mediated autoimmunity by inhibiting the proliferation of T lymphocytes, inducing CD4 + T-cell apoptosis and increasing the proportion of immunoinhibitory T reg cells, and its application may improve the clinical outcome of patients with severe aplastic anemia. 18,19 Additionally, Zhu et al 9 demonstrated that ATO induced the upregulation of PD-L1 in oral squamous carcinoma cells. Consistent with previous studies, we found that ATO significantly upregulated the expression of PD-L1 at both the protein and mRNA levels in NB4 and Jurkat cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that ATO induced upregulation of PD-L1 in solid tumor cells. 9 To verify its effect on leukemia cells, ATO was used to treat NB4 and Jurkat cells for 24 h. As shown in Figure 1(A), ATO significantly enhanced the expression of PD-L1 at the protein level in NB4 and Jurkat cells compared with that in the control group cells. Due to glycosylation of the PD-L1 protein, 1-3 bands were apparent in the results.…”
Section: Ato-induced Pd-l1 Upregulation In Leukemia Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IHC staining procedure was processed as described previously (Zhu et al, 2020). In brie y, the tissue microarray slides were depara nized in xylene and gradient ethanol.…”
Section: Immunohistochemistry (Ihc) Stainingmentioning
confidence: 99%
“…Tumor cells frequently generate and secrete reactive oxygen species (ROS) and the resulting oxidative stress in the tumor microenvironment is now emerging as a potent PD-L1 inducer. Many studies have reported high PD-L1 expression associated with high generation of ROS but no direct link between these two observations has been investigated [200][201][202][203][204][205][206][207].…”
Section: Redox Regulation Of Pd-l1mentioning
confidence: 99%